Tax Minimization Moderate Transfer Pricing - Lidya Manda Sari; Arisandy, Nelsi (Universitas Muhammadiyah Surakarta, 2024)
The Corruption Eradication Commission (KPK) sniffed out potential tax evasion through a transfer pricing scheme on alleged illegal nickel ore export practices to China. KPK Deputy for Prevention and Monitoring Pahala Nainggolan said that his agency is currently reviewing if there are weaknesses in the nickel governance system. The system in question is the Coal Mineral System or Simbara, which was launched in March 2022. The population of this study is mining sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) from the period 2020 – 2023. Determination of samples in this study using the purposive sampling method. The number of samples used was 18 companies with 72 research units. The source of data in this study is taken from the company's published annual report. Testing in this study using E-Views 12 software. The results of the study based on the panel data regression analysis test showed that debt convenant and intangible assets had an effect on transfer pricing, while the size of the company and the bonus mechanism did not affect transfer pricing. Tax minimization is able to moderate the relationship between company size, debt convenant, intangible assets, and bonus mechanisms for transfer pricing.